2021
DOI: 10.3389/fpsyg.2021.719403
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Team Reflexivity During the COVID-19 Lockdown: A Qualitative Study of Multi-Vision Groups In-person and Online

Abstract: Introduction: The professional self is often hindered by a lack of self-care and poor work-life balance, and cannot be considered an unlimited resource. Given this, the reflexive team is an important organizational tool for protecting workers' well-being. The non-profit organization Maestri di Strada (MdS) (“Street Teachers”) conducts action research (AR) in the area of socio-education. The main tool used by the group to protect the well-being of its members is a guided reflexivity group, inspired by the Balin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…However, the participants explained that the collaboration and group commitment to achieve their goals remained unchanged. In this regard, it has been found that the construction of a reflective group constitutes a protective factor for the well-being of workers ( Parrello et al, 2021 ). The implementation of the group through the online mode was experienced by some participants as a critical issue, as there were, at least initially, difficulties linked to both emotional involvement and personal interactions, particularly for those who experience challenges speaking and interacting with strangers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the participants explained that the collaboration and group commitment to achieve their goals remained unchanged. In this regard, it has been found that the construction of a reflective group constitutes a protective factor for the well-being of workers ( Parrello et al, 2021 ). The implementation of the group through the online mode was experienced by some participants as a critical issue, as there were, at least initially, difficulties linked to both emotional involvement and personal interactions, particularly for those who experience challenges speaking and interacting with strangers.…”
Section: Discussionmentioning
confidence: 99%
“…as well as for professions that work mainly online. As Parrello et al (2021) point out reflective group work can be an organizational tool to maintain the well-being of workers, even more useful during the lockdown period linked to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The whole course is supported by reflexing spaces both for students (e.g. circle time) as well as educators and peer educators, through the Multivision Group (Parrello et al, 2019;Parrello et al, 2021). Educators pay particular attention to the student-school relationshiptheir achievements in the TTW are carefully communicated to their teachers, and the latter are invited to students' performances.…”
Section: Contextmentioning
confidence: 99%